O Programa Universidade para Todos (ProUni): um estudo do perfil dos bolsistas e da perspectiva de gestores de uma instituição privada de ensino superior de Belo Horizonte - Liliane Gonçalves Fernandes de Lima (2020)
This research’s objective is to delineate the profile and the academic’s trajectory of the current ProUni’s scholar in the Brazilian context and a private institution from the city of Belo Horizonte. For this, were used: (i) secondary data from the Brazilian Higher Education Census and documentary sources generated by the investigated institution; (ii) and primary data obtained in semi-structured interviews with the institution managers. The results show that the profile of the student attended by the program partially differs from the general profile of the private higher education student in Brazil, as from the students’ profile of the investigated institution, which it’s becoming more affluent in the course of the last years. Such results confirm socio-logical theories about the segregated democratization in the process of expansion and massification of higher education, as viewed from the analysis about the existence of “horizontal inequalities” that condition the access and success of the less advantaged social groups.